Pioneering Social Research : Life Stories of a Generation - Thompson, Paul (Book collections on Project MUSE., 2021)
Presenting the landmark Pioneers life stories project, this one-of-a-kind book documents how modern social research in the UK was shaped. It combines a fascinating history of the generations who built outstanding and influential social research with a valuable resource for future research and teaching on methods.